Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
|3x-7| -x = 7
|3x - 7| = 7 +x
Th1: 3x -7 = 7+x
3x -x = 7 +7
2x = 14
x= 14:2
x=7
Th2: 3x - 7 = -(7+x)
3x -7 = -7 -x
3x +x = -7 +7
4x =0
x=0
Vậy x= 7 và x=0
Bài 1:
a: \(\Leftrightarrow\left\{{}\begin{matrix}\left(3-2x\right)^2=\left(x-2\right)^2\\x< =\dfrac{3}{2}\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}\left(2x-3-x+2\right)\left(2x-3+x-2\right)=0\\x< =\dfrac{3}{2}\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}\left(x-1\right)\left(3x-5\right)=0\\x< =\dfrac{3}{2}\end{matrix}\right.\Leftrightarrow x=1\)
b: \(\left|x\right|< 3\)
nên -3<x<3
c: \(\left|x\right|\ge5\)
nên \(\left[{}\begin{matrix}x\ge5\\x\le-5\end{matrix}\right.\)
Bài 2:
\(\Leftrightarrow\left\{{}\begin{matrix}x+1=0\\y-7=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=-1\\y=7\end{matrix}\right.\)